Acetylated histone variant H2A.Z is involved in the activation of neo-enhancers in prostate cancer. Issue 1 (December 2017) - Valdés-Mora, Fátima; Gould, Cathryn; Colino-Sanguino, Yolanda; Qu, Wenjia; Song, Jenny; Taylor, Kylie; Buske, Fabian; Statham, Aaron; Nair, Shalima; Armstrong, Nicola; Kench, James; Lee, Kenneth; et al.
Abstract Acetylation of the histone variant H2A.Z (H2A.Zac) occurs at active promoters and is associated with oncogene activation in prostate cancer, but its role in enhancer function is still poorly understood. Here we show that H2A.Zac containing nucleosomes are commonly redistributed to neo-enhancers in cancer resulting in a concomitant gain of chromatin accessibility and ectopic gene expression. Notably incorporation of acetylated H2A.Z nucleosomes is a pre-requisite for activation of Androgen receptor (AR) associated enhancers. H2A.Zac nucleosome occupancy is rapidly remodeled to flank the AR sites to initiate the formation of nucleosome-free regions and the production of AR-enhancer RNAs upon androgen treatment. Remarkably higher levels of global H2A.Zac correlate with poorer prognosis. Altogether these data demonstrate the novel contribution of H2A.Zac in activation of newly formed enhancers in prostate cancer. Acetylation of the histone variant H2A.Z at gene promoters is associated with oncogene activation; however, it is unclear if such modification has a role in regulating the function of enhancers. Here the authors show that acetylated H2A.Z is redistributed at cancer neo-enhancers and regulates the activity of specific enhancers of cancer-related genes.